Application of Safety Procedure As Efforts To Prevent Work Accidents In MT. Serang Jaya Engine Room - Herda , Riocevin; Hermanto, Andy Wahyu; Yuntoro, Kresno (Politeknik Ilmu Pelayaran Semarang, 2024)
Safety Procedure is a formal written safety procedure and contains procedures, identification and obligations to carry it out while working. Not optimal due to lack of understanding of Safety Procedures that pose a risk of work accidents. This study aims to determine the causes and impacts of the non-optimal implementation of Safety Procedures and efforts so that the Safety Procedure can run optimally so as to prevent work accidents in the engine room. The research method used in this study is a qualitative method with a descriptive pattern. Research data sources are obtained from primary and secondary data. Data collection techniques through observation, literature study, interviews and documentation during the time researchers carried out marine practices on the MT ship. Serang Jaya. The data analysis techniques used are by collecting data, reducing data, presenting data and drawing conclusions or verifying data which is also supported by fishbone analysis. Testing the validity of data using the tringulation method. The results stated that the factors of not optimal Safety Procedure due to lack of crew understanding of Safety Procedure, and crew concern for safety as well as lack of supervision and coordination between crew and management are the reasons why Safety Procedure cannot run optimally. The impact of not optimal Safety Procedure is the high risk of work accidents, hampering ship operations, harming the ship or the parties concerned. Efforts that can be made to optimize this are by carrying out Safety meeting activities, Toolbox Meeting, Drill, installing Safety Signs. And always provide counseling related to Safety Procedure in the engine room.